The methodology of health care training in the conditions of interaction medical specialists – children and adults with special needs - Zheleva, Elena (Student Niepełnosprawny. Szkice i Rozprawy, 2019)
The methodology of health education is devoted to a particularly important problem - the training of medical specialists for working with children and adults with special needs. This requiresfrom her, in her probation at higher education institutions to train medical specialists: to learn and apply her main accents in dealing with these persons; to form highly qualified medical professionals to identify, perform and evaluate activities related to their own role in caring for a person with special needs - a child or an adult.